Effects of Constant and Fluctuating Low Temperatures on the Development of Aedes aegypti (Diptera: Culicidae) from a Temperate Region. Issue 6 (29th May 2019) - De Majo, María Sol; Zanotti, Gabriela; Campos, Raúl E; Fischer, Sylvia
Abstract: Most studies of the effects of low temperature on the development of immature stages of Aedes aegypti (L.) have been performed at constant temperatures in the laboratory, which may not accurately reflect the variable environmental conditions in the field. Thus, the aim of this study was to assess the effect of constant temperatures (CT) and fluctuating low temperatures (FT) on the fitness of Ae. aegypti of Buenos Aires, Argentina. Three CT treatments (12, 14, and 16°C) and three FT treatments (12, 14, and 16°C ± 4°C) were performed and then survival, development time, and size of adults analyzed for each treatment. The immature stages completed development in all the treatments, with an average survival of 88% at 16°C, 85% at 14°C, and 22% at 12°C, and showed no differences between the CT and FT treatments. Development times were similar between the CT and FT treatments at 16°C (average ± SD: 22.7 ± 2.0 d) and at 14°C (average ± SD: 30.5 ± 2.5 d), whereas at 12°C, they lasted longer under CT (average ± SD: 46.6 ± 5.1 d) than under FT (average ± SD: 37 ± 6.5 d). The sizes of the adults at 12 and 14°C were similar but larger than those at 16°C, and showed no differences between the CT and FT treatments. Compared to populations of other geographical regions assessed in previous studies, the shorter development times and the high survival at 14 and 16°C, and the ability to complete development at 12°C, a fact not previously reported, suggest that the Ae. aegypti population of Buenos Aires city has a higher tolerance to these conditions.